2017
DOI: 10.1007/s10551-017-3720-2
|View full text |Cite
|
Sign up to set email alerts
|

Does Deceptive Marketing Pay? The Evolution of Consumer Sentiment Surrounding a Pseudo-Product-Harm Crisis

Abstract: The slandering of a firm's products by competing firms poses significant threats to the victim firm, with the resulting damage often being as harmful as that from product-harm crises. In contrast to a true product-harm crisis, however, this disparagement is based on a false claim or fake news; thus, we call it a pseudo-product-harm crisis. Using a pseudo-product-harm crisis event that involved two competing firms, this research examines how consumer sentiments about the two firms evolved in response to the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 46 publications
0
13
0
2
Order By: Relevance
“…This opens some exciting research opportunities. For example, individual and cultural differences regulate the amount of risk consumers are willing to take on (Avnet and Higgins 2006;Song et al 2017). Managers and consumers often interpret the adoption of new technology as a risky endeavor.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…This opens some exciting research opportunities. For example, individual and cultural differences regulate the amount of risk consumers are willing to take on (Avnet and Higgins 2006;Song et al 2017). Managers and consumers often interpret the adoption of new technology as a risky endeavor.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…e product-harm crisis is a knotty issue created by defective or dangerous products [6,7]. As shown in a previous study [8], the episode of a product-harm crisis includes initial negative event, firm's recovery strategy, and post-recovery.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, Song et al (2017) studied deceptive marketing and slanderous practices online, and found that “while both firms suffered, the damage to the offending firm (which spread fake news to cause the crisis) was more detrimental, in terms of advertising effectiveness and negative news publicity, than that to the victim firm (which suffered from the false claim).” In short, ethical considerations aside, foul play online simply may not pay.…”
Section: Ethical Considerations For the Use Of Social Media In Negotimentioning
confidence: 99%